Curriculum renewal in engineering through theory-driven evaluation : final report 2014. - Jolly, Lesley (Australia. Office for Learning and Teaching, 2014)
This report details the outcome of an evaluation of a widespread curriculum renewal in engineering education, the adoption of the Engineers Without Borders (EWB) Challenge projects into first-year curricula. This evaluation targets outcomes at two levels. The first addresses engineering education and initiatives such as the EWB Challenge and its sequels which respond to long-standing calls for reform in the discipline. The second is generic to curriculum renewal generally and what needs to be known for greatest efficacy. Overall the conclusion is that use of the EWB Challenge provides good opportunities for pursuing the desired changes to learning outcomes for engineering students, although other kinds of projects could be equally successful as long as some basic principles are followed. The third-world settings provided by the EWB projects were interestingly different for most students but were also seen as too remote from experience and ultimate career goals by others. Most of the learning goals could be addressed through any real-world project. [Executive summary, ed]